The Influence of demographic factors on the attitudes Dispositions of secondary school students toward physical activity - Mohammed, Ahmed Qasim; Mohammed, Warhel Asim; Saleh, Ibrahim Mohameed (Journal of Physical Education, 2023)
The primary objective of this study is to discern the inherent disposition of sports activity among students in the preparatory stage. Additionally, the study endeavors to ascertain the statistical importance of disparities in these attitudes based on gender (male and female), academic focus (scientific and literary), and academic year (tenth and eleventh). The investigation adopts a comparative descriptive methodology, and the study sample comprises a randomly selected cohort of 1435 students encompassing both genders. Rigorous assessment of the scale's validity and reliability was undertaken, and subsequently, the amassed data underwent statistical analysis using the SPSS software. The outcomes of the analysis disclose that students exhibit a favorable outlook on physical activity in a general context. Intriguingly, the analysis further indicates the absence of statistically significant differentiation in students' attitudes towards physical activity concerning the variables of gender, academic specialization, and grade. In light of these findings, it is recommended that concerted endeavors are channeled towards provisioning the requisite material and human resources to augment the landscape of scholastic sports. Moreover, a focused emphasis on physical education curriculum is encouraged, with the intent to enhance student awareness and foster more positive attitudes towards active engagement in sports.